#TITLE_ALTERNATIVE# - ADISTY ALAMANDA (NIM: 12206023); Pembimbing: Dr.Ir.Taufan Marhaendrajana, PRISILA
Many methods can be applied to obtain the maximum amount of oil from resevoir, one of which is hydraulic fracturing. The purpose of hydraulic fracturing is to increase the productivity of the well / formation. Prior to hydraulic fracturing, there are several parameters that must be designed first. Parameters to be considered in the design are the direction of fracture, fracture length, fracture width, height of fracture, and others. Technical parameters in a hydraulic fracturing design is dependent on reservoir properties. For example, the direction of fracture have to perpendicular to the least principal stress of a reservoir, the fracture height must consider whether there is shale zone or the water zone. Reservoirs are reviewed in this study is the oil reservoir with a sandstone with bottom water drive. Reservoir model without fracture made the basic case that can be compared with the existing reservoir model after the hydraulic fracture. This study was conducted using simulators to be able to model and know the results that will be analyzed further. This study aimed to evaluate the influence of the water zone located beneath the reservoir of the hydraulic fracturing design. Comparative value of productivity index and cumulative oil production with a base case of fracture cases analyzed so that can know the hydraulic fracturing design best applied from a reservoir model is used. The final results of this study is an analysis of hydraulic fracturing design is influenced by bottom water drive.